Discrimination of Axial and Central Stereogenic Elements in Chiral Bis(oxazolines) Based on Atropisomeric 3, 3′‐Bithiophene Scaffolds Through Chiroptical Spectroscopies. Issue 10 (27th September 2016) - Gabrieli, Sara; Mazzeo, Giuseppe; Longhi, Giovanna; Abbate, Sergio; Benincori, Tiziana
Abstract: Two diastereoisomeric pairs of bis‐oxazolines, provided with a stereogenic center at carbon 4 and based on the 3, 3′‐bithiophene atropisomeric scaffold, were synthesized and structurally characterized. They differ in the substituents at positions 2 and 5 of the thiophene rings, which are functionalized with methyl (1) or phenyl (2) groups, respectively. In vibrational circular dichroism (VCD) spectra, recorded in CCl4 solutions, it is possible to distinctly recognize the characteristic features of axial and central stereogenic elements. In tandem with Density Functional Theory (DFT) calculations, the absolute configuration (AC) of the diastereoisomers was safely established. In this case, VCD was shown to be superior to ECD (electronic circular dichroism) in the assignment of AC. The normal modes, evaluated from DFT calculations, show that the VCD signals in correspondence with the stereogenic axis of the bithiophene unit are different for 1 and 2. The VCD spectra of a molecular analog of 1, the (S)‐2, 2′, 5, 5′‐tetramethyl‐4, 4′‐bis‐(diphenylphosphino)‐3, 3′‐bithiophene oxide (3), characterized by the same 3, 3′‐bithiophene scaffold, but devoid of stereogenic centers, exhibits signals similar to those observed in the case of diastereoisomer (aS, R, R)‐1a, associated with almost identical normal modes. Chirality 28:686–695, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :